Pertarungan Narasi Islam dalam Pemilihan Presiden Tahun 2019 - Aswar, Hasbi; Zamzami, Fauzi Wahyu; Widjayanti, Alifya Kasih; Priyansyah, Ahmad (State Islamic Institute of Kudus (IAIN Kudus), 2022)
The 2019 general election is one of the most intense elections in Indonesia's history, especially after reformasi (political reform) in the 1998. This election did not only involve political parties in the fight for the presidency but also involves opposition movements, especially the Islamic movement. After the phenomenon of 212 in 2016, Islamic movements became very active in influencing political activities in Indonesia, including the elections held in 2019. The efforts of this Islamic opposition movement were to delegitimize the regime (Joko Widodo) who tried to participate in the 2019 re-election through various narratives including religious narratives in it. Meanwhile, on the other hand, there are also other Islamic groups that carry out counter-narratives and support Jokowi to be re-elected in the 2019 election. This study focuses on discussing the narratives and counter-narratives carried out by Muslim opposition and pro-regime Islamic groups in the 2019 elections through narrative analysis in qualitative research. Data is collected through online sources, both from those with affiliation with related movements and other media. This research found that there were two sides of the Islamic narrative in the 2019 presidential election, namely the Islamist side who criticized the incumbent presidential candidate and the Islamic group side who supported the presidential candidate as well as the president who was in power.